The Art of Collage in Jewish Liturgy: Compilations of Biblical Verses in Pesuqei De-Zimra - Rodman, Peretz A. (Hebrew studies, 2018)
Several passages in classical Jewish liturgy consist of biblical verses, assembled mostly from the book of Psalms, without introduction or additions. Two such passages, which appear in the preliminary prayers ( 'verses of song') before the standard morning worship, mix and match verses from several psalms to form independent literary works. These works present a distinct theological statement different from any made by any of their constituent verses. Biblical authority is marshaled to assure the worshipper of the reliability of God's eventual salvation and to give support to the worshipper's appeal that God restore to the Jews their former status and their ancestral land.